Pola Pikir Penggunaan Bahasa Inggris Pada Masyarakat Perkotaan di Jabodetabek - Reza Amarta Prayoga; Husnul Khatimah (Universitas Trunojoyo Madura, 2019)
This research is motivated by the problem of penetration of foreign language in urban society. The mindset of English usage in urban society is symbolically represented that foreign languages must be mastered and used in daily life. It becomes a new outbreak of modern life that slowly puts foreign languages, especially English in a higher position than Indonesian language. The English usage as the primary language is considered to symbolize prestige and promise a better position and socioeconomic standard. Therefore, this study aims to describe the mindset of urban society about the English usage in Jabodetabek (Jakarta, Bogor, Depok, and Bekasi). This is a descriptive qualitative research, the instrument in collecting data in the field is conducted through in-depth interview and observation. Meanwhile, the secondary data obtained through literature research related to the research topics. The results shows that the English usage has become the social behavior of urban society in Jabodetabek. English usage represents some symbols, ie. higher educational status, upper middle social class, and modern and classy lifestyle. This causes English is superior to Indonesian as a national language. This reality becomes an early indication of the weakening of the Indonesian language in the public sphere (Government, Corporation, Education, and Mass Media). Slowly but surely English becomes the symbol of prima donna language among urban society in Jabodetabek.